2008
DOI: 10.1007/s10404-008-0319-z
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric characterisation of a dual-stream electrochemical microfluidic device

Abstract: A microfluidic device is presented with offchip electrodes residing in a reservoir and connected via micro-capillaries to the Y-shaped microfluidic channel. The device is tested by potentiometric measurements involving dual-stream laminar flow of two aqueous solutions carrying different electrolytes at various concentrations. Open circuit potentials are measured for a series of solutions of alkali metal chlorides and tetraalkylammonium chlorides as well as for dilute hydrochloric acid. The open circuit potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…The diffusion potential is established within milliseconds after the two streams come into contact [23]. In previous measurements [30], we investigated the influence of the liquid flow rates on the measured potential peaks. It was found that the height of the potential peaks did not depend on the experimentally accessible flow rates, only the peak width increased with decreasing flow rates, due to a longer residence time of the liquids in the microchannel at slower flow rates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The diffusion potential is established within milliseconds after the two streams come into contact [23]. In previous measurements [30], we investigated the influence of the liquid flow rates on the measured potential peaks. It was found that the height of the potential peaks did not depend on the experimentally accessible flow rates, only the peak width increased with decreasing flow rates, due to a longer residence time of the liquids in the microchannel at slower flow rates.…”
Section: Resultsmentioning
confidence: 99%
“…As described previously [30,32], the measured open circuit potential, j oc , is a combination of the diffusion potential, j d , and the potential difference between the electrodes, j e , caused by the difference in chloride concentrations in the opposing reservoirs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be a membrane between two well stirred solutions. Experimentally, the situation of a watery boundary can also be be realised in microchannels, involving dual-stream laminar flow of two aqueous solutions along each other carrying different electrolyte salts at various concentrations [18][19][20][21][22] forming a flowing junction [17]. potential using the Henderson equation [20] and numerical solutions of the Nernst-Planck equation [21,22] and the measured open-cicuit potentials has been found.…”
Section: Introductionmentioning
confidence: 99%